Changes during medical treatments before adenotonsillectomy in children with obstructive sleep apnea. Issue 4 (August 2022) - Kajiyama, Taihei; Komori, Masahiro; Hiyama, Mariko; Kobayashi, Taisuke; Hyodo, Masamitsu
Abstract: Objectives: The severity of pediatric obstructive sleep apnea (OSA) can vary from mild to very severe (AHI ≥ 30 events/h) with the seasons. The efficacy of medical treatment has been investigated in cases of mild and moderate pediatric OSA, but not in severe cases thoroughly. Methods: Our prospective cohort study involved 205 children who visited our outpatient clinic between December 2014 and May 2020. We performed home sleep tests after the initial visit, and then polysomnography after optimizing the control of rhinitis, sinusitis, adenoid hypertrophy, and tonsillitis by using medical treatments. Results: The respective proportions of patients who improved to obstructive AHI (O-AHI) < 1/h or who proceeded to surgery were 43.4% and 62.3% in mild cases; 43.3% and 52.2% in moderate cases; 30.2% and 68.4% in severe cases; and 0.0% and 100% in very severe cases. Additionally, nadir SaO2 improved significantly between before and after medical treatment in both O-AHI < 1/h and O-AHI ≥ 1/h patients (respectively p < 0.0001, p = 0.0009). The lowest nadir SaO2 before medical treatment was 74% in patients in whom O-AHI was normalized after medical treatments. Conclusion: Medical treatment instituted before a surgical decision is made can provide substantial benefits and avoid unnecessary surgery if there is time for such treatments. In contrast, it may be difficult to normalize the O-AHI in pediatric patients with very severe OSA or a nadir SaO2 of less than 74% by medical treatment.